2014
DOI: 10.1021/ja5107282
|View full text |Cite
|
Sign up to set email alerts
|

Activation of White Phosphorus by Low-Valent Group 5 Complexes: Formation and Reactivity of cyclo-P4 Inverted Sandwich Compounds

Abstract: We report the synthesis and comprehensive study of the electronic structure of a unique series of dinuclear group 5 cyclo-tetraphosphide inverted sandwich complexes. White phosphorus (P4) reacts with niobium(III) and tantalum(III) β-diketiminate (BDI) tert-butylimido complexes to produce the bridging cyclo-P4 phosphide species {[(BDI)(NtBu)M]2(μ-η3:η3P4)} (1, M = Nb; 2, M = Ta) in fair yields. 1 is alternatively synthesized upon hydrogenolysis of (BDI)Nb(NtBu)Me2 in the presence of P4. The trinuclear side prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 56 publications
(107 reference statements)
1
29
0
Order By: Relevance
“…striking for instance that the gold(III) complex (BDI Xy,Me )Au(Me) 2 undergoes protonation at the BDI methine carbon when treated with 1 eq. 110 In the solid-state, short CvN bond lengths are observed, in agreement with localized double imine bonds and a non-planar H 2 C(C(Me)NAr) 2 ligand core with the sp 3 hybridized methylene carbon lying below the plane defined by the two CvN imino moieties. 111 In the presence of 2 eq.…”
Section: Scheme 19mentioning
confidence: 56%
See 1 more Smart Citation
“…striking for instance that the gold(III) complex (BDI Xy,Me )Au(Me) 2 undergoes protonation at the BDI methine carbon when treated with 1 eq. 110 In the solid-state, short CvN bond lengths are observed, in agreement with localized double imine bonds and a non-planar H 2 C(C(Me)NAr) 2 ligand core with the sp 3 hybridized methylene carbon lying below the plane defined by the two CvN imino moieties. 111 In the presence of 2 eq.…”
Section: Scheme 19mentioning
confidence: 56%
“…HOTf, rather than protonolysis of an Au-Me bond, as shown in Scheme 24, bottom. 110 HOTf, further protonation of this system occurs at the ligand resulting in the formation of the triflate salt [HC{C(Me) NHAr} 2 ][OTf ] (Ar = 2,6-Me 2 C 6 H 3 ).…”
Section: Scheme 19mentioning
confidence: 99%
“…61 Compounds 130 and 131 were surprisingly unreactive and were even stable in the presence of oxygen and water under ambient conditions over weeks. 61 Compounds 130 and 131 were surprisingly unreactive and were even stable in the presence of oxygen and water under ambient conditions over weeks.…”
Section: Scheme 27mentioning
confidence: 99%
“…Cummins, for example, has shown that disproportionation of a niobium(IV) tris(enolate) in the presence of P 4 provides the {P 8 } cluster compound 1 ,[3] while in a very recent report, Bergman and Arnold have described a trinuclear β-diketiminato μ-P 12 niobium complex, which was isolated as one of multiple minor by-products during the reaction of the Nb V complex ( Dipp BDI)Nb(N t Bu)Me 2 ( Dipp BDI=HC{C(Me) 2 N(2,6- i Pr 2 C 6 H 3 )} 2 ) with H 2 in the presence of P 4 . [4] Notably, this latter reaction gave a compound containing a cyclo-P 4 dianion as its predominant reaction product and, in some respects, the irrationality of the formation of both of these compounds is typical of the synthesis of high-nuclearity {P n } clusters. [1f]…”
mentioning
confidence: 99%
“…[12] As a first step toward the functionalization of white phosphorus catalyzed by a Group 2 metal, we present in this contribution the results of our initial study, which indicate that remarkable kinetic control during P 4 activation is achievable with organomagnesium reagents (Scheme 1). Key to the success of this chemistry is the application of the sterically demanding Dipp BDI supporting ligand, which was employed in the syntheses of Arnold and Bergman’s aforementioned niobium systems,[4] compounds 2 and 3 , and very recently described binuclear cobalt(I) and copper(I) species containing a P 4 -derived tetraphospacyclobutadiene and an unactivated P 4 ligand respectively. [13]…”
mentioning
confidence: 99%